Leksikon Aktivitas Pengolahan Gambir di Kabupaten Lima Puluh Kota - Memory Hidayat; Rona Almos; Reniwati Reniwati (Universitas Andalas, 2018)
This article describes the classification and the meaning of the lexicon that exists in gambir processing activities in Lima Puluh Kota District. The theoretical framework used is anthropolinguistics. Methods and techniques for providing data use the SLC method, note-taking technique, and record technique. Methods and data analysis techniques using PUP techniques and HBB techniques.Based on the results of the analysis found lexicon forms of words and phrases. The number of lexicon data found was 72 words and 15 phrases. Also, 34 lexicon data were subjected to morphological processes. As for the grouping of gambier processing activities in Lima Puluh Kota Regency, namely naming parts of fields, opening fields, nurseries, clearing fields, picking gambier leaves, and gambier processing terms.